Determinants of MSME Income: The Role of Capital, Education Level, and Financial Literacy in Manufacturing MSMEs - Sinaga, Gilbert Johan Martin (Department of Accounting, Faculty of Economics, Universitas Nurtanio Bandung, 2026)
This study aims to examine the effects of capital, education level, and financial literacy on the income of Micro, Small, and Medium Enterprises (MSMEs) in Bengkalis Regency. A quantitative approach was employed using a survey method involving 390 MSME actors selected through purposive sampling. Data were collected through structured questionnaires and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that capital, education level, and financial literacy have positive and significant effects on MSME income, with financial literacy emerging as the most dominant factor. These findings suggest that, beyond traditional production factors, the ability to effectively manage financial resources plays a critical role in enhancing business performance. This study contributes to the literature by integrating production theory and human capital theory in explaining MSME income, while also highlighting the importance of financial literacy in the context of small businesses in regional economies. Practically, the findings underscore the need to strengthen financial literacy and human resource capacity as strategic approaches to improving MSME income.